The interplay between glioblastoma and microglia cells leads to endothelial cell monolayer dysfunction via the interleukin‐6‐induced JAK2/STAT3 pathway. Issue 11 (1st April 2019) - Couto, Marina; Coelho‐Santos, Vanessa; Santos, Liliana; Fontes‐Ribeiro, Carlos; Silva, Ana Paula; Gomes, Célia M. F.
Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumor, with an average life expectancy of 12–15 months. GBM is highly infiltrated by microglial cells (MG) promoting tumor growth and invasiveness. Moreover, microglia activation and subsequent neuroinflammation seem to be involved in blood–brain barrier (BBB) dysfunction commonly observed in several central nervous system diseases, including brain tumors. Nevertheless, how the crosstalk between microglia and tumor cells interferes with BBB function is far from being clarified. Herein, we evaluated the effects of reciprocal interactions between MG and GBM cells in the barrier properties of brain endothelial cells (ECs), using an in vitro approach. The exposure of ECs to the inflammatory microenvironment mediated by MG‐GBM crosstalk induced a decrease in the transendothelial electric resistance and an increase in permeability across the ECs (macromolecular flux of 4 kDa‐fluorescein isothiocyanate and 70 kDa‐Rhodamine B isothiocyanate–Dextran). These effects were accompanied by a downregulation of the intercellular junction proteins, β‐catenin and zonula occludens. Moreover, the dynamic interaction between microglia and tumor cells triggered the release of interleukin‐6 (IL‐6) by microglia and subsequent activation of the downstream Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) pathway. Interestingly, the depletion of IL‐6 or the blockade of the JAK/STAT3 signaling with AG490 were able to prevent the EC hyperpermeability. Overall, we demonstrated that IL‐6 released during MG‐GBM crosstalk leads to barrier dysfunction through the activation of the JAK/STAT3 pathway in ECs and downregulation of intercellular junction proteins. These results provide new insights into the mechanisms underlying the disruption of BBB permeability in GBM. Abstract : Microglia‐glioblastoma crosstalk triggers the release of interleukin‐6 (IL‐6) from microglia, which via activation of the Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathway leads to endothelial cells (ECs) dysfunction, with defects on intercellular junction proteins expression, decreased transendothelial electric resistance, and increased paracellular permeability. The sequestration of IL‐6 with a specific neutralizing antibody or blockade of the JAK2/STAT3 pathway with the JAK2 inhibitor AG490 prevents the disruption of ECs monolayers.